2015
DOI: 10.1186/s13048-015-0192-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral administration of low-dose follicle stimulating hormone on hyperandrogenized mice as a model of polycystic ovary syndrome

Abstract: BackgroundPolycystic Ovary Syndrome (PCOS) is a widespread reproductive disorder characterized by a disruption of follicular growth and anovulatory infertility. In women with PCOS, follicular growth and ovulation can be induced by subcutaneous injections of low doses of follicle stimulating hormone (FSH). The aim of this study was to determine the effect of oral administration of recombinant human FSH (rhFSH) on follicle development in a PCOS murine model. Moreover, since it is unlikely that intact rhFSH is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…PCOS was induced according to some previous articles [17][18][19]. Wistar female rats were subcutaneously injected with DHEA (6 mg/100 g, Wuhan Huamei Technology Group Co., Ltd., Wuhan, China) into the back and neck (once a day for 20 d).…”
Section: Pcos Induction and Groupingmentioning
confidence: 99%
“…PCOS was induced according to some previous articles [17][18][19]. Wistar female rats were subcutaneously injected with DHEA (6 mg/100 g, Wuhan Huamei Technology Group Co., Ltd., Wuhan, China) into the back and neck (once a day for 20 d).…”
Section: Pcos Induction and Groupingmentioning
confidence: 99%
“…Thus, the regulation of level of LH has become a target in the treatment of PCOS. A recent study reported that treatment with myo-inositol can significantly improve the hormonal parameters by decreasing the level of LH, which in turn improved the conditions of PCOS [ 19 ]. In another study, orally administrated FSH was found to significantly reduce the severity of PCOS in a mouse model by reducing the number of cystic follicles and restoring estradiol level [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…All rats used in this study had normal estrous cycles prior to treatment, as confirmed by examination of vaginal smears under a light microscope for two sequential cycles (about 8–10 days). The PCOS rat model was established according to a previous study [ 24 ]. Briefly, the animals were subcutaneously injected with 6 mg/100 g dehydroepiandrosterone (DHEA) in the neck once a day for 20 consecutive days.…”
Section: Methodsmentioning
confidence: 99%